Analisa Data Mining Untuk Prediksi Penjualan Produk Menggunakan Algoritma FP-Growth Berbasis Web Studi Kasus Online Shop Muslim Galeri - Kanisisus Heatubun, Petrus; Fansyuri, Maulana (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
Online Shop Muslim Galeri is one of the sellers of contemporary products in the field of clothing and goods, in sales in the era of globalization 4.0, Muslim Galeri is certainly in the business of selling using technology or manually by offering directly to potential consumers. Random sales provide a very unpredictable picture in predicting product sales, it is certainly very difficult to know the progress or decline of sales of what products are sold to the Muslim Gallery. The problem that exists in Muslim galleries is the need to predict product sales to consumers. With this, Data Mining will be applied in this study as a solution to predict the sales of Muslim Gallery products.The method used in the data processing process is using the FP-Growth algorithm. Data processing using this algorithm is expected to provide an easy solution in predicting product sales at the Muslim Gallery Online Shop.